Noninvasive estimation of pulmonary vascular resistance improves portopulmonary hypertension screening in liver transplant candidates. Issue 7 (5th June 2019) - DesJardin, Jacqueline T.; Manicardi, Marcella; Svetlichnaya, Yana; Kolaitis, Nicholas A.; Papolos, Alexander I.; Selby, Van N.; Zier, Lucas S.; Klein, Liviu; Aras, Mandar A.; Yao, Francis Y.; Roberts, John P.; De Marco, Teresa
Abstract: Despite limitations in sensitivity and specificity, estimation of the pulmonary artery systolic pressure (ePASP) on echocardiography is used for portopulmonary hypertension (PoPH) screening in liver transplant (LT) candidates. We proposed that alternative echocardiographic models, such as estimated pulmonary vascular resistance (ePVR), may provide improved testing characteristics in PoPH screening. In a retrospective analysis of 100 LT candidates, we found that the formula ePVR = ePASP/VTIRVOT + 3 if MSN (VTIRVOT = right ventricular outflow tract time velocity integral; MSN = mid‐systolic notching of the VTIRVOT Doppler signal) significantly improves accuracy of PoPH screening compared to ePASP. We determined the optimal ePVR cutoff for PoPH screening to be 2.76 Wood units, as this cutoff provided 100% sensitivity and 73% specificity in screening for clinically significant PoPH. Comparatively, ePASP at a cutoff of 40 mm Hg provided 91% sensitivity and 48% specificity. We devised a new screening algorithm based on the use of ePVR at intermediate ePASP values (35‐54 mm Hg), and we confirmed the testing characteristics of this algorithm in a separate validation cohort of 50 LT candidates. In screening LT candidates for PoPH, the ePASP lacks accuracy, leading to unnecessary RHCs and undiagnosed cases of PoPH. A screening algorithm which incorporates the ePVR may be more reliable.